Analisa Kekuatan Impak Sambungan Las Gesek Dengan Variasi Waktu Pada Dua Material Baja Aisi 1040 Dengan SS 400 - Abriansyah, Fadhlurrohman; Sugiyarto, Sugiyarto; Somawardi, Somawardi (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Welding plays an important role in every metal working and repair in the production process. There are various methods to overcome problems in the meterial connection process. One of them is friction welding which is one of the solutions in solving metal joining problems. In this study, the method used is the RSM (Response Surface Method) method which aims to determine the value of impact strength on AISI 1040 steel which is connected to SS 400 steel which has been carried out the Friction Welding process. This study uses an impact test in accordance with the standard ASTM E23 impact test charpy method with a size of 55 mm × 10 mm × 10 mm with a notch depth of 2 mm, and a notch angle of 45 °. The impact test was conducted using the Charpy method impact testing machine model JB-300B. With a pendulum capacity of 150 Joules. Based on the results of the impact test, the largest value was obtained in the 6th and 7th experiments with an impact price value of 2.575 joules/mm2, while the smallest value was in the 3rd experiment with a value of 1.557 joules/mm2